"The Role of Ethical Marketing Practices for Marketing Communication Activities in Achieving Marketing Superiority: Comparative Applied Study between the Opinions of Customers of Telecommunications Companies Operating in Saudi Arabia and Egypt" - Mamdouh, Mamdouh (The Arab Journal of Administration, 2022)
The aim of this Study is to investigate the Compatibility, Correlation and Impact between Ethical Marketing (EM) Practices of Integrated Marketing Communications (IMC) Activities and Marketing Superiority (MS) while Revealing the Differences in Evaluation by Customers of Telecommunications Companies Operating in Saudi Arabia and Egypt, Provide Recommendations for the Development of Service and Marketing Reality for these Companies, The Modest Enrichment of this Quality of Rare Studies. The Researcher used the Descriptive Analytical Method based on Two Types of Data (Secondary and Primary), Using a Questionnaire of 62 Items distributed to a Sample of Corporate Customers (420 People) Via Facebook, Twitter, email, and WhatsApp, The Number of Correct Questionnaires Stood at 408 (97%). The Researcher used Methods: Descriptive Statistics, Chi- Square, Pearson Correlation, Regression Analysis, and Analysis of Variance. The Statistical Package SPSS V.23 was used to analyze the Study Data which showed that there is a Compatibility, Correlation and Influential Relationship between (EM) for (IMC) and (MS), And that there are Significant Differences in the Evaluation of the Respondents for each of the Activities of (IMC) and (MS) according to the Different Telecommunications Company dealing. The Study recommended the need of using Various Means of Advertising with Wide Coverage, Attention to the System and Content of the Internal Presentation, The Salesman should have Sufficient Information and Providence of a Clear and Honest Image of the Company and its Services, The information Officer will be able to speak and provide Accurate Information, Identify Customers’ Reactions to the Services provided and display the Results transparently.